A usable past : essays in European cultural history - Bouwsma, William J. (William James), 1923-2004 (University of California Press, 1990)
The essays assembled here represent forty years of reflection about the European cultural past by an eminent historian. The volume concentrates on the Renaissance and Reformation, while providing a lens through which to view problems of perennial interest. A Usable Past is a book of unusual scope, touching on such topics as political thought and historiography, metaphysical and practical conceptions of order, the relevance of Renaissance humanism to Protestant thought, the secularization of European culture, the contributions of particular professional groups to European civilization, and the.